Effects of elemental sulfur application rates on soil Al3+ solubility and its concentration in maize plants (Zea mays L.) - M., Karimizarchi; H., Aminuddin; O., Radziah (Universiti Putra Malaysia Press, 2017)
A greenhouse experiment was conducted to elucidate the influence of soil acidification due to application of different doses of elemental sulphur (0, 0.5, 1.0 and 2.0 g S kg-1 soil) on Al3+ solubility at 0, 20 and 40 days after incubation. Maize plants were grown after soil treatment with the elemental S and were allowed to grow for 45 days. The results showed that addition of elemental sulphur significantly increased the soil acidity; each g S decreased soil pH for 1.52 units. The Al3+ concentration in soil remained rather unchanged from the pH value of 7.3 to around 5 and experienced a 22000-time increase at the pH value of 4. Soil acidification from the background of 7.03 to 6.29 resulted in 41.83% increase in root Al3+ concentration and it was not significantly affected with further soil acidification. Soil acidification progressively decreased Al3+ concentration in the stem but it failed to affect Al3+ concentration in the leaves. The optimum rate of sulphur for maize without the risk of Al3+ toxicity under greenhouse conditions was 0.82 g S kg-1 soil. Further evaluation under field conditions is required.